Influence of Ag2O Nanoparticles on the Ammonia Gas Sensing Properties of CNT/P3HT Composite Films - Haydar Abdulmeer Abbas; Wissem Cheikhrouhou-Koubaa (Journal of Techniques)
In this research, the CNT/P3HT and CNT/P3HT@Ag2O composite films were prepared to be utilized as the ammonia gas sensor. Moreover, the impact of the synthesized composites on ammonia gas sensing and the effect of Ag2O nanoparticles on the properties of the composites were examined. The layers were analyzed using XRD, AFM, FTIR, and gas sensing analysis, providing insights into their potential for improving ammonia gas sensing. Despite changes in the P3HT to CNT ratios, the XRD analysis of the CNT/P3HT and CNT/P3HT@Ag2O composite films revealed the same structural properties for the carbon nanotubes. In accordance with the data obtained from the FTIR test of the composite films, characteristic P3HT bands and various functional groups were detected. As the gas sensing analysis indicated, the sensitivity increased with the increasing ratio of P3HT to CNT, and the highest sensitivity was achieved by the CNT/P3HT (0.7) sensor. Moreover, the addition of silver oxide further increased the sensitivity. These results suggest that the CNT/P3HT@Ag2O film sensor is highly sensitive to ammonia gas and can be a promising sensor for the detection of ammonia gas.